Enfermedades en cultivos de yuca asociados con maiz y name en Cordoba, Bolivar, Sucre y Atlantico - Laberry, R.; Lozano, J.C. (1988)
The incidence and severity of several diseases affecting cassava in monoculture and in association with maize and/or yam in the departments of Cordoba, Bolivar, Sucre, and Atlantico (Colombia) were assessed. Leaf spots (brown leaf spot, white leaf spot, blight leaf spot) and CBB were the most common diseases. The distribution of CBB, anthracnose, superelongation, and E.T. disease (cord-like formations) in this region is discussed. Healthy planting material (not infected with bacterioses or superelongation) should be used. Cuttings taken from crops infected with superelongation should be immersed for 10 min. in a solution with benomyl (3g/l), captafol (4 g/l), or Sistemin (2 cc/l). Cassava/maize intercropping was excellent in areas where bacterioses is endemic. Bacterioses-infected monocropped cassava can be pruned towards the end of the rainy season to reduce disease severity. In intercropped cassava/yam, the yam competition reduced the cassava stand; therefore this practice is not recommended. (CIAT)